THE EFFECT OF USING THE COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH IN TEACHING SPEAKING - Umar Haliwanda (Elite : English and Literature Journal, 2021)
This research examines the use of communicative language teaching (CLT) in enhancing students' speaking for instances fluency, accuracy, and clarity. The researchers found that two problems faced by the students at SMK Negeri 1 Bener Meriah. Firstly the problem came from the student's side such as insecure/lack of confidence, lack of vocabulary, shyness/shame, etc. The second problem is the aspects graded of speaking i.e fluency, accuracy, and clarity. The researcher focused on fluency, accuracy, and clarity in teaching speaking in the classroom by using the communicative language teaching (CLT) approach rather than using the grammar-translation method (GTM). The research method applied in this research was experimental quantitative research because the researchers want to know the cause and effect of two variables. The researcher found that there is a significant difference in students' ability after being taught by using the communicative language teaching (CLT) approach rather than used grammar-translation method (GTM).